Conjunto de bases gaussianas universal para átomos de Rb até Xe - Cruz, Henrique Raulino Coelho da (2013)
In this work we generate Universal Gaussian basis sets, uncontracted and with segmented contraction, for the atoms from Rb through Xe. These sets were generated from a single sequence containing 26 exponents, obtained from the DZP (Barros and collaborators, 2010) basis set. From the single sequence we get all Gaussian functions required to construct a base for each atom, obeying the criterion of lowest total HF energy. Also a segmented contraction schema was proposed for the studied atoms and, polarization and diffuse functions were added to the set. We applied our Universal sets, uncotracted and contracted, to perform theoretical calculations of equilibrium geometries, electric dipole moments and polarizabilities for some molecular systems, and comparisons were made with theoretical results obtained from adapted Gaussian basis set of similar size, and with experimental results. From this comparisons we found that our contracted universal set is appropriate for calculating molecular properties